2009
DOI: 10.1002/anie.200900900
|View full text |Cite
|
Sign up to set email alerts
|

All Kinds of Reactivity: Recent Breakthroughs in Metal‐Catalyzed Alkyne Chemistry

Abstract: Alkynes of reactions: Recent breakthroughs in metal‐catalyzed alkyne reactions, which expand the synthetic utility of alkynes, have been achieved. These approaches broaden the range of alkynes that are accessible by CN and CC bond‐forming reactions and demonstrate that the use of bifunctional heterobimetallic catalysts can lead to new reactivity and excellent enantioselectivity (see scheme).magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…This result might be explained by ligand exchange of Cr II , allowing nucleophilic substitution of labile ligands (e.g., Cl) to give nucleophilic chromium(II) acetylide 15 . Indeed, like Zn II , Cu I , or Au I acetylides that are generated in situ from terminal alkynes at room temperature upon treatment with an organic base (TEA, i Pr 2 N n Pr, or NH 4 OH) [13,15c,15d,29] by ligand exchange, this substitution reaction occurs for Cr II . This mechanism is supported by kinetic studies reported by Merbach, who showed that this ligand exchange is kinetically very fast and favored for Cr II , whereas Cr III is known to be extremely resistant to this process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result might be explained by ligand exchange of Cr II , allowing nucleophilic substitution of labile ligands (e.g., Cl) to give nucleophilic chromium(II) acetylide 15 . Indeed, like Zn II , Cu I , or Au I acetylides that are generated in situ from terminal alkynes at room temperature upon treatment with an organic base (TEA, i Pr 2 N n Pr, or NH 4 OH) [13,15c,15d,29] by ligand exchange, this substitution reaction occurs for Cr II . This mechanism is supported by kinetic studies reported by Merbach, who showed that this ligand exchange is kinetically very fast and favored for Cr II , whereas Cr III is known to be extremely resistant to this process.…”
Section: Resultsmentioning
confidence: 99%
“…[13] Classical methods have mainly exploited the relatively high acidity of terminal acetylenic C–H bonds to form metal alkynylides, either by direct metalation using strong bases, such as n -butyllithium or lithium diisopropylamide at low temperature (−100 to −80 °C), [14] or upon treatment with tertiary amines in the presence of a stoichiometric or catalytic amount of the metal salt of interest (Figure 1, route a). [15] Lithium and silver acetylides prepared by this approach are also utilized for the preparation of other acetylides by transmetalation with magnesium, zinc, cerium, and other metals (Figure 1, route b). [1620] Alternatively, lithium acetylides can also be prepared through the Fritsch– Buttenberg–Wiechell (FBW) rearrangement/metalation of 1,1-dibromoolefins when treated with an excess amount of n -butyllithium (Figure 1, route d).…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] When picoline-derived complex 1 a is allowed to react with C 2 H 2 in C 6 H 6 (2 bar, 90 8C, 16 h, Scheme 4) under strictly anaerobic and anhydrous conditions, quantitative conversion (according to 1 H NMR spectroscopy) into the novel four-membered iridacycle 5 a is observed. Heating to 120 8C yields instead the related complex 6 a, whereas if water is not removed carefully from commercially obtained C 2 H 2 or the reaction solvent, acetyl complex 7 a may become the main reaction product independently of temperature.…”
mentioning
confidence: 99%
“…[9] This is in many ways akin to the biosynthetic machinery,i nw hich natural products are built on an enzymatic assembly line. [12][13][14][15][16][17] Thegeneration of metal s-and p-complexes with alkynes can be accomplished by similar and often identical catalyst systems;m ore importantly,b oth nucleophilic and electrophilic reactivity profiles can be realized from the same components. [11] We reasoned that alkynes could offer an interesting template for orthogonal tandem catalysis because they can be activated by two distinctly different modes,e ither by end-on or side-on manifolds,t hereby allowing different types of reactivity to be accessed.…”
mentioning
confidence: 99%
“…[11] We reasoned that alkynes could offer an interesting template for orthogonal tandem catalysis because they can be activated by two distinctly different modes,e ither by end-on or side-on manifolds,t hereby allowing different types of reactivity to be accessed. [12][13][14][15][16][17] Thegeneration of metal s-and p-complexes with alkynes can be accomplished by similar and often identical catalyst systems;m ore importantly,b oth nucleophilic and electrophilic reactivity profiles can be realized from the same components.…”
mentioning
confidence: 99%